Private lives of public women: Photos of sex workers (minus the sex) in South Korea. (January 2013) - Cheng, Sealing
We mostly learn about women in prostitution through representation by non-sex-workers: activists, policy-makers, journalists, and academics. What comes through are often hypersexualized and essentialized images of sex workers as either victims or agents. This dichotomy not only essentializes their lives but also undermines women as partners for engagement. Against this background, what could be learned from photographs taken by women in prostitution of their everyday lives? How do they supplement or challenge existing discourses of prostitution? What do the photographers and viewers get out of such an endeavor? And finally, what do the quotidian aspects of life have to do with research on sex work and sexuality in general? These are some of the questions this essay raises through the author's experience of organizing an exhibition of photographs taken by women in a South Korean red-light district in 2009. The project took place at a time when these women's lives were undergoing dramatic change at the intersection of neoliberal development and anti-trafficking projects, materialized in the demolition of the red-light district and increasing criminalization of prostitution in South Korea. Between October 2009 and April 2010, 40 of these photographs went on a traveling exhibition "Our Lives, Our Space: Views of Women in a Red-Light District" on the east coast of the USA. This article discusses some of the impact that the exhibition has had on its viewers and the photographers. It concludes by suggesting how a study of prostitution "minus the sex" could point to new avenues of sexuality studies.